L’obbedienza al diritto tra ragioni e cause - Farano, Alessia (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2021)
The paper targets the interaction between new neuroscientific findings on decision-making and the theoretical concept of legal obedience. Beyond the naturalistic framework, it will be argued that every legal system requires a specific model of agency, in whose definition the scientific claims have now a prominent role. The classic model of rational agent, issued from the Penal Enlightment, will be challenged with respect to three main neuroscientific assumptions. The first one will be the reduction of the experience of agency under coercion; the second one will be the increasing role of emotions in the understanding of the so called ‘neuromoral network’; the last one will be the ‘bounded rationality’ giving rise to nudging policies.